Some physical characteristics and their relationship to shooting accuracy among Dhi Qar University football team players (Global Scientific Review, 2023)
The game of football is the most popular game in the world. This game depends on the importance of general and specific physical characteristics, which are the main foundation for performing the basic skills of the game, in which each player bears a high burden of specific and general physical requirements. The importance of research is evident in highlighting some specific physical characteristics. This is done by studying the correlation between them and the skill of shooting football in order to achieve the best achievement. The problem of the research is that there are most matches There is a lack of interest in the development of special physical attributes among some coaches, especially those attributes that are directly related to the skill of shooting in football. The research aims to identify some physical attributes and their relationship to accurate shooting. The players of the University of Dhi Qar football team. Assuming the research, there is a significant correlation between some physical characteristics and the skill of shooting in football for the players of the University of Dhi Qar team. As for the human field, the players of the Dhi Qar University team, the Zamani stadium of the College of Physical Education and Sports Sciences / University of Dhi Qar, and the temporal field For the period The time period from 10/4/2022 until 4/1/2023 included the research methodology and field procedures. The researcher used the descriptive approach to suit the nature of the research problem. The research community was identified, represented by Dhi Qar University football players, who numbered (18). The goalkeepers, who numbered (18), were excluded. 2) After that, (10) players were randomly selected using a lottery method, as the sample constituted 55.55% of the research population. One of the most important recommendations is to emphasize the interest in training the element of strength characterized by speed and its effective role in performing motor skills, especially the skill of aiming, and attention to physical characteristics in the training units in general. Giving it enough time for its effective role and its basic connection to the basic motor skills of football.